Analisis Penyebab Kematian Maternal Di Kabupaten Garut (Studi Epidemiologi dalam Upaya Menurunkan Kematian Maternal di Provinsi Jawa Barat) - Dhita Aulia Octaviani; Farid Husin; Firman F. Wirakusumah; Hadi Susiarno; Hadyana Sukandar; Dadan Susandi (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2019)
Maternal mortality is still a problem globally and especially occur in developing countries, including Indonesia. The maternal mortality rate is one indicator of the health status of a country. Garut is one part of West Java province with the count of maternal mortality case was 45 deaths in 2015. Most of the causes of maternal death is preventable, ie factors of patients, healthcare workers, facilities, and referral. Recording and reporting of maternal deaths has not to be going well yet, so that intervention can not be set to decrease maternal mortality significantly.Research carried out by sequential explanatary mixed method. The first phase, data collection and analysis is done quantitatively, followed by collection of qualitative data in the second phase which aims to strengthen the results of quantitative research. Quantitative research using cross sectional and qualitative study using in-depth interviews and focus group discussions.The study was conducted in October-November, 2016.Based on the research showed that 96% of maternal deaths occur in Garut regency are preventable maternal deaths that caused by multifactorial, a combination of healthcare workers factors, patient factors, and referral factors. Maternal deaths are also caused by the referral process has been delayed. Besides that, recording and reporting have not been able to run well, with the availability of human resources, but the existing policy has not been adequate.Patient factors such as age, parity, and birth spacing is at risk, as well as negative perceptions of mothers and families to health facilities contributed to preventable maternal deaths. Health workers factor prefer to unqualified health workers in conducting effective communication and counseling. Access, financing, and poor communication between health professionals and patients have contributed to the occurrence of resistance in the referral process.